Mokhnacheva O. V. The character identity in terms of the genre experiment in the contemporary novel (The Sense of an Ending by J. Barnes) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article considers one of the aspects of the genre strategy of the novel at the present stage of its development – the status of the character as a center-forming factor in the interplay with the artistic form and text structures. Basing on a particular example, the tragedy of the “I” identity has been traced, as well as the problem of the corresponding the character'sidentity to temporal continuum.
Keywords: novel; genre experiment; heroʼs identity